Characteristics of krypton ion emission from a gas field ionization source with a single atom tip. (25th April 2017) - Shichi, Hiroyasu; Matsubara, Shinichi; Hashizume, Tomihiro
Abstract: A scanning ion beam instrument equipped with a gas field ionization source (GFIS) has been commercialized, but only helium and neon are currently available as GFISs. The characteristics of krypton ion emission from a single atom tip (SAT) have not been reported yet. In this study, the characteristics of krypton ion emission were investigated by field ion microscopy. At 65 K, the krypton ion emission current reached approximately 40 pA, which is 1 order of magnitude higher than that at 130 K. As the krypton gas pressure was increased, the krypton ion current increased. At a pressure of 0.3 Pa, the emission current was anticipated to reach 200 pA, which may be high enough for nanofabrication. The variation of the krypton ion current was as low as 5% in one hour. We concluded that a krypton ion beam instrument equipped with a GFIS will be a powerful tool for nanofabrication.